Synthesis and Evaluation of Some Sulfonamide-Substituted of 1,3,5-Triphenyl Pyrazoline Derivatives as Tyrosinase Enzyme Inhibitors - Herfindo, Nofal; Frimayanti, Neni; ikhtiarudin, Ihsan; eryanti, Yum; zamri, Adel (Universitas Jenderal Soedirman, 2023)
Pyrazoline is well-known as heterocycles compound that can exhibit many biological effects. In this work, we synthesized a series of sulfonamide-substituted 1,3,5-triphenyl pyrazoline compounds as a promising tyrosinase inhibitor agent. These compounds prepared by multicomponent reaction of corresponding aldehyde, ketone, and hydrazine using seal-vessel reactor. Pyrazolines compound were tested for their tyrosinase inhibitor activity through in vitro assay. The test result found that compound 4c, 4d, and 4e possessed better tyrosinase inhibitory activity compared to the reference drug, kojic acid. Compound 4c exhibited the strongest tyrosinase inhibitory effect with an IC50 value of 30.14 µM. The results suggested that hydroxyl and methoxy substituent at para position are preferable. Furthermore, molecular docking studies result match the pattern of in vitro assay where the compound will provide a stronger binding interaction and lower binding free energies.